Implementasi Everyday English Expression Di SMAN 1 Gerung - Sudewi, Ni Ketut Putri Nila; Ramdhani, Suciaty; Syahid, Agus; Miswaty, Titik Ceriyani; Pramanaputra, Abiyyu Alghozy (CV. Global Cendekia Inti, 2024)
The